2003
DOI: 10.1001/archneur.60.8.1100
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Antiepileptic Drug Treatment in Juvenile Myoclonic Epilepsy

Abstract: Lamotrigine and topiramate are effective alternative options to valproic acid in the treatment of JME. Lamotrigine is an effective option as monotherapy and polytherapy. Topiramate is an effective option as polytherapy, but more data are needed to determine if it is an effective option as monotherapy. More effective therapy is needed to improve myoclonic seizure control. Older AEDs, such as phenytoin and carbamazepine, may not be indicated in JME patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
4
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 17 publications
2
61
4
5
Order By: Relevance
“…In patients with JME, it was initially shown that TPM was effective in cases refractory to other AED 10 , and later its efficacy was demonstrated in patients with recent onset epilepsy and intolerable side effects of other AED 4,5,8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with JME, it was initially shown that TPM was effective in cases refractory to other AED 10 , and later its efficacy was demonstrated in patients with recent onset epilepsy and intolerable side effects of other AED 4,5,8 .…”
Section: Discussionmentioning
confidence: 99%
“…TPM in an average dose of 663 mg/day improved s e i z u re f requency in 11 patients, maintained control in t w o and led to worsening in two. In the series of Prasad et al 5 , TPM used in a minimum effective dose of 230 mg in monotherapy and 250 mg in polytherapy was considered to be an alternative to VPA . Tolerability to TPM was lower than to VPA, which the authors attributed to excessively rapid titration of the drug; in this series, one of the 19 patients showed worsening of the seizures.…”
Section: Discussionmentioning
confidence: 99%
“…A case series also found TPM to be effective when used as combination therapy in JME [21,Class III]. A pilot study comparing VPA and TMP in patients with newly diagnosed JME (or patients who never received VPA or TPM for JME) found the medications to be similarly effective, but with different adverse event profiles [27,Class II].…”
Section: Topiramatementioning
confidence: 99%
“…The efficacy of LTG in IGE is unquestionable (Morris et al, 2004;Prasad et al, 2004). Nevertheless, there may be cases in which LTG is not effective.…”
mentioning
confidence: 99%